Design of a rollover index-based sliding mode controller for roll stability of three wheeled vehicles using rear differential braking - Ketemaw, Daniel; Seid, Solomon (Frontiers in Mechanical Engineering, 2022)
Urban vehicles (like tricycle and bicycle vehicle) are made to handle issues with traffic, air pollution, energy use, and parking restrictions in big cities. However, they are more susceptible to rollovers and stability problems because they are smaller and narrower than normal cars. Now a day, Vehicle manufacturers place a lot of emphasis on the dynamic stability of their products. As a result, develop dynamic model to predict and detect the risk of rollover and designing a controller to reduce it in a delta type configuration of tricycle vehicle is the major concern of this paper. On the basis of a two degree of freedom (2-DOF) bicycle model, develop rollover dynamics, and design state observer for sideslip angle, sliding mode and fuzzy logic controller are the major concern of this paper. The suggested rollover index (RI) accuracy has been evaluated by simulation using a high-fidelity CarSim. The performance analysis to determine the effectiveness of thus proposed controller is conducted using MATLAB/Simulink integrated with the Carsim software. Simulation results with three scenarios are shown with and without the control system. The outcome of the simulation demonstrated that fuzzy sliding mode controller (FSMC) and a fuzzy logic controller can reduces the chance of a vehicle rolling over accident.